Recent advances in the development of liquid crystalline nanoparticles as drug delivery systems - Leu, Jassica S. L.; Teoh, Jasy J. X.; Ling, Angel L. Q.; Chong, Joey; Loo, Yan Shan; Mat Azmi, Intan Diana; Zahid, Noor Idayu; Bose, Rajendran J. C.; Madheswaran, Thiagarajan (Multidisciplinary Digital Publishing Institute, 2023)
Due to their distinctive structural features, lyotropic nonlamellar liquid crystalline nanoparticles (LCNPs), such as cubosomes and hexosomes, are considered effective drug delivery systems. Cubosomes have a lipid bilayer that makes a membrane lattice with two water channels that are intertwined. Hexosomes are inverse hexagonal phases made of an infinite number of hexagonal lattices that are tightly connected with water channels. These nanostructures are often stabilized by surfactants. The structure’s membrane has a much larger surface area than that of other lipid nanoparticles, which makes it possible to load therapeutic molecules. In addition, the composition of mesophases can be modified by pore diameters, thus influencing drug release. Much research has been conducted in recent years to improve their preparation and characterization, as well as to control drug release and improve the efficacy of loaded bioactive chemicals. This article reviews current advances in LCNP technology that permit their application, as well as design ideas for revolutionary biomedical applications. Furthermore, we have provided a summary of the application of LCNPs based on the administration routes, including the pharmacokinetic modulation property.